2021
DOI: 10.3390/nu13103629
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Levels in Children with Obesity Are Associated with Metabolic Risk and Inflammatory Parameters

Abstract: Melatonin, the hormone of circadian rhythm regulation, is involved in the modulation of mitochondrial activity through its antioxidant and anti-inflammatory properties. Alteration of circadian rhythms such as sleep is related to obesity and metabolic pathogenesis in adulthood, but studies during childhood are scarce. The present study investigated the association of melatonin with metabolic and inflammatory markers in children with (n = 113) and without obesity (n = 117). Melatonin was measured in saliva four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…Our previous studies [44] found decreased melatonin levels in overweight children. Another study indicated increased melatonin levels in obese people [45]. The authors attributed this to the fact that melatonin, which is involved in antioxidant and anti-inflammatory protection, may be activated in the context of obesity as a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…Our previous studies [44] found decreased melatonin levels in overweight children. Another study indicated increased melatonin levels in obese people [45]. The authors attributed this to the fact that melatonin, which is involved in antioxidant and anti-inflammatory protection, may be activated in the context of obesity as a compensatory mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…Уровень мелатонина у детей с ожирением повышался в течение 1 ч сна, что рассматривалось как компенсаторный механизм. Предполагают, что увеличение образования мелатонина стимулирует сонливость, увеличивает время сна и направлено на противодействие провоспалительным и оксидативным эффектам, вызванным ожирением и недостатком сна [76]. Предполагают, что прием мелатонина, благодаря его противовоспалительному, антиоксидантному и седативному действию, может быть полезен для регуляции метаболических процессов при ожирении.…”
Section: нарушения снаunclassified
“…The level of melatonin in children with obesity increased during 1 h of sleep, which was up-regulated in the context of obesity as a compensatory mechanism. The organism triggered its production to increase drowsiness, promote behaviors that increased sleep time or counteract the pro-inflammatory and antioxidant effects caused by obesity and lack of sleep [ 157 ]. Therefore, the improvement of sleep disorders by melatonin may be of great significance in the regulation of obesity.…”
Section: Potential Mechanisms Of Melatonin In Obesitymentioning
confidence: 99%